2019
DOI: 10.23893/1307-2080.aps.05724
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of topical gel containing nanostructured lipid carriers dispersion of an antifungal drug

Abstract: Fungal infection are the common dermatological diseases. Drug delivery systems for topical use have shown significant advantages in targeting the drug to the action site in the body and also reduces the systemic side effects.In the present study an attempt was made to prepare econazole nitrate loaded nanostructured lipid carrier (NLC). Different formulations were prepared by hot homogenization technique using solid lipid and liquid lipid (GMS, GMO) and surfactants (Poloxamer 188, Poloxamer 407). Formulations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Incorporating an increased ratio of Sterotex NF: GMS sustained the drug release, and this might be due to the increased consistency of the formulation, due to the high molecular weight of Streotex NF compared to GMS. Increasing the percentage of oils retarded VCZ release from MLNCs, which might be accredited to the higher viscosity and increased thickness of lipid layer, which acted as a barrier in the way of the drug, thereof sustaining its release (Gujjar et al, 2019 ). The results suggested that VCZ is incorporated in MLNCs and this guarantee its slow release to prolong the contact time and so maximizing the efficacy (Wang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating an increased ratio of Sterotex NF: GMS sustained the drug release, and this might be due to the increased consistency of the formulation, due to the high molecular weight of Streotex NF compared to GMS. Increasing the percentage of oils retarded VCZ release from MLNCs, which might be accredited to the higher viscosity and increased thickness of lipid layer, which acted as a barrier in the way of the drug, thereof sustaining its release (Gujjar et al, 2019 ). The results suggested that VCZ is incorporated in MLNCs and this guarantee its slow release to prolong the contact time and so maximizing the efficacy (Wang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The viscometer was run at various revs, and the reading in centipoises (cps) was recorded. 20 Drug content estimation 7.4 Ph phosphate buffer was used to dilute 1 mL of 5-Flucytosineloaded SLN carrying gel. It was ultracentrifuged for 30 min at 4°C at 4000 rpm, and then the vesicles were disrupted with the appropriate amount of water.…”
Section: Viscositymentioning
confidence: 99%